Cardiac c-Kit Biology Revealed by Inducible Transgenesis. Issue 1 (22nd June 2018) - Gude, Natalie A.; Firouzi, Fareheh; Broughton, Kathleen M.; Ilves, Kelli; Nguyen, Kristine P.; Payne, Christina R.; Sacchi, Veronica; Monsanto, Megan M.; Casillas, Alexandria R.; Khalafalla, Farid G.; Wang, Bingyan J.; Ebeid, David E.; et al.
Abstract : Rationale: : Biological significance of c-Kit as a cardiac stem cell marker and role(s) of c-Kit+ cells in myocardial development or response to pathological injury remain unresolved because of varied and discrepant findings. Alternative experimental models are required to contextualize and reconcile discordant published observations of cardiac c-Kit myocardial biology and provide meaningful insights regarding clinical relevance of c-Kit signaling for translational cell therapy. Objective: : The main objectives of this study are as follows: demonstrating c-Kit myocardial biology through combined studies of both human and murine cardiac cells; advancing understanding of c-Kit myocardial biology through creation and characterization of a novel, inducible transgenic c-Kit reporter mouse model that overcomes limitations inherent to knock-in reporter models; and providing perspective to reconcile disparate viewpoints on c-Kit biology in the myocardium. Methods and Results: : In vitro studies confirm a critical role for c-Kit signaling in both cardiomyocytes and cardiac stem cells. Activation of c-Kit receptor promotes cell survival and proliferation in stem cells and cardiomyocytes of either human or murine origin. For creation of the mouse model, the cloned mouse c-Kit promoter drives Histone2B-EGFP (enhanced green fluorescent protein; H2BEGFP) expression in a doxycycline-inducible transgenic reporter line. The combination of c-Kit transgenesis coupled to H2BEGFP readout provides sensitive, specific, inducible, and persistent tracking of c-Kit promoter activation. Tagging efficiency for EGFP+/c-Kit+ cells is similar between our transgenic versus a c-Kit knock-in mouse line, but frequency of c-Kit+ cells in cardiac tissue from the knock-in model is 55% lower than that from our transgenic line. The c-Kit transgenic reporter model reveals intimate association of c-Kit expression with adult myocardial biology. Both cardiac stem cells and a subpopulation of cardiomyocytes express c-Kit in uninjured adult heart, upregulating c-Kit expression in response to pathological stress. Conclusions: : c-Kit myocardial biology is more complex and varied than previously appreciated or documented, demonstrating validity in multiple points of coexisting yet heretofore seemingly irreconcilable published findings. Abstract : Supplemental Digital Content is available in the text.